Analisis Sistem Pengendalian Realisasi Pajak Daerah pada Pemerintah Kabupaten Sekadau Tahun 2022-2024 - Enjelina Vernika; Renny Wulandari; Rina Mayasafitri (Jurnal Akuntansi, Auditing dan Investasi, 2026)
Regional Original Revenue (PAD) of the Sekadau Regency Government is derived from four components: local taxes, regional levies, management of separated regional assets, and other legitimate regional revenues. The value of these revenue components, particularly local taxes, has shown a decline despite the implementation of a realization control system. This study aims to analyze the internal control system for local tax realization in Sekadau Regency based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework, which consists of five components: control environment, risk assessment, control activities, information and communication, and monitoring. This research utilizes a descriptive qualitative method, involving five respondents related to local tax management. Data collection techniques included observation, interviews, documentation, and questionnaires. The collected data were processed and analyzed using flowchart analysis and questionnaire evaluation. The findings indicate that while the internal control system is functioning well, there are still weak points that require further attention.